Black swan : The force of the unpredictable in modern society - Ostojić, Jovana (2023)
The purpose of this thesis is to explore the concept of Black Swan events and the connection between uncertainty, risk-taking, and having a personal stake in the outcome, or “skin in the game”, in relation to those events. The main aim is to determine whether individuals with skin in the game are more willing to take risks that may lead to hazard and financial distress, compared to those without a personal stake in the outcome. To address this question, the results of a study on family and non-family businesses conducted by Gottardo and Moisello are analyzed. The results suggest that family businesses were less likely to experience financial crisis compared to non-family-owned businesses and that having a personal stake in the success of the business may be associated with more careful decision-making and lower risk of financial distress.